Analyzing EFL university learners’ positionings and participation structures in a collaborative learning environment - Montenegro, Aida (Colombian Applied Linguistics Journal, 2012)
A preliminary analysis about the way a group of university students behaved in group activities that promoted interaction and negotiation revealed that some students were positioned negatively while learning English. This qualitative study analyzed the learners’ positionings as group members and the participation structures under a specific pedagogical intervention focused on peer collaboration. The data collection instruments were audio recordings, field notes and individual conferences. The conclusions show that the rights and responsibilities during group work were given according to the way the learners mutually acknowledged their skills. The school and social skills recognized by the peers were related to checking each others’ work, building consensus, and guiding the development of the task.